Organizational Innovation - Kaplan, Howard B. author. aut Link
IX, 239 p.
Keywords: Innovation in the private and public sectors has been the subject of a great deal of study, since it is central to the economic growth and effective governance of most organizations. Determining the changes needed in an organization is less difficult than determining how to make the changes work. This volume is the result of a three-year study that investigated the factors associated with the implementation of program changes in a nonprofit community welfare agency. The results of the research showed that a greater understanding of the implementation process was needed, both by the workers and administrators. In addition, factors other than "need" were determined to influence what action is taken to implement the recommendations. This book takes the results of the study and demonstrates how implementation can be successful in an organization. This work includes factors such as administration behavior and perception, its effect on board members, mobility orientation, job satisfaction, and the prediction of program change and will be of interest to management in both the private and non-profit sector as well as students of organizational sociology and psychology.